2017
DOI: 10.1111/acer.13467
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol and Road Traffic Injuries in Latin America and the Caribbean: A Case-Crossover Study

Abstract: Background This study reports dose-response estimates for the odds ratio (OR) and population attributable risk of acute alcohol use and road traffic injury (RTI). Methods Data were analyzed on 1,119 RTI patients arriving at 16 emergency departments (EDs) in Argentina, Brazil, Costa Rica, Dominican Republic, Guatemala, Guyana, Mexico, Nicaragua, Panama and Trinidad & Tobago. Case-crossover analysis, pair-matching the number of standard drinks consumed within the six hours prior to the RTI with two control per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 32 publications
2
24
2
Order By: Relevance
“…In this sense, there are few data on differences of BAC levels among drivers and passengers in the literature. Recent evidence shows that, even though ORs seem to be higher in passengers compared to drivers, there are no statistical differences that might provide evidence of potential bias on this regard [29]. In addition, not having the time when the collision occurred and the time when the necropsy was conducted made it impossible to identify whether those car occupants classified as negative for alcohol were not actually under the influence at the moment of the collision.…”
Section: Discussionmentioning
confidence: 99%
“…In this sense, there are few data on differences of BAC levels among drivers and passengers in the literature. Recent evidence shows that, even though ORs seem to be higher in passengers compared to drivers, there are no statistical differences that might provide evidence of potential bias on this regard [29]. In addition, not having the time when the collision occurred and the time when the necropsy was conducted made it impossible to identify whether those car occupants classified as negative for alcohol were not actually under the influence at the moment of the collision.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Borges and co-worker reported dose-response estimates for the odds ratio (OR) and population attributable risk of acute alcohol consumption and road traffic injury (RTI) (Borges et al, 2017). In this study the data was obtained and analyzed from 1,119 RTI patients who reached 16 emergency departments in countries like Trinidad and Tobago, Dominican Republic, Brazil, Guatemala, Costa Rica, Guyana, Nicaragua, Panama, Mexico, and Argentina.…”
Section: Alcohol Abuse and Social Implicationsmentioning
confidence: 99%
“…Applying local and global measures immediately in areas like Latin America and the Caribbean to decrease consumption of alcohol can reduce usage of alcohol among pedestrians, drivers, and passengers involved in RTI (WHO, 2010;Borges et al, 2017).…”
Section: Alcohol Abuse and Social Implicationsmentioning
confidence: 99%
“…Despite improved hospital care, mortality from RTAs is the second leading public health problem in the Islamic Republic of Iran (2). There is strong evidence that a substantial number of fatal as well as nonfatal injuries results from alcohol consumption and abuse (3); therefore, it can be argued that alcohol consumption is one of the most well-known risk factors for RTAs (4,5). High alcohol consumption was attributed to 14% of all road traffic injuries and the rate of alcohol consumption in RTAs has been reported to vary from 14% to 26% (4,6).…”
Section: Introductionmentioning
confidence: 99%
“…There is strong evidence that a substantial number of fatal as well as nonfatal injuries results from alcohol consumption and abuse (3); therefore, it can be argued that alcohol consumption is one of the most well-known risk factors for RTAs (4,5). High alcohol consumption was attributed to 14% of all road traffic injuries and the rate of alcohol consumption in RTAs has been reported to vary from 14% to 26% (4,6). It is reported that the chance of an accident after alcohol consumption is 6.1 times higher than without alcohol consumption (7).…”
Section: Introductionmentioning
confidence: 99%